Dielectric Behaviour of Diethylene Triamine + Trigol Mixtures Using Microwave Techniques - Kalamse, G.M.; Nimkar, M.J. (Asian Journal of Chemistry, 2010)
In the present paper we have obtained the values of dielectric constant (ε´) and loss factor (ε") experimentally by using Serber's method, for the binary mixtures of diethylene triamine (DETA) and trigol (TG) at 10.7 GHz microwave frequency and 20ºC temperature. Molar polarization, apparent polarization and the excess values of permitivities (Δε´, Δε"), square of refractive index (Δn2D), viscosity (Δη) and activation energy (ΔEa) of viscous flow estimated from the measured dielectric data. We have used these parameters to explain the nature of complex formation. The results suggest the strong interactions between the molecules of amine and trigol.